Longstanding proliferation of CD3 negative large granular lymphocytes preceding the development of high grade non-Hodgkin's lymphoma. Issue 7 (July 1995) - Smith, S R; Middleton, P G; Birch, P J; Morgan, L; Saunders, P W
Abstract : A patient with a persistent CD3 negative large granular lymphocyte (LGL) proliferation with immunophenotypic and functional characteristics of natural killer cells is described. The LGL proliferation persisted and six years after diagnosis the patient developed a high grade B cell non-Hodgkin's lymphoma. Molecular studies demonstrated clonal B cell populations in the peripheral blood, distinct from that identified in the lymphoma, both at presentation with non-Hodgkin's lymphoma and at complete remission following combination chemotherapy. It is postulated that T cell dysregulation associated with the CD3 negative LGL proliferation may have led to B cell dysfunction and loss of normal B cell control, with the subsequent development of a clonal B cell lymphoproliferative disorder.